2006
DOI: 10.1016/j.reprotox.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of lycopene on cisplatin-induced changes in sperm characteristics, testicular damage and oxidative stress in rats

Abstract: The aim of this study was to investigate the possible protective role of lycopene on cisplatin (CP)-induced spermiotoxicity using quantitative, biochemical and histopathological approaches. Adult male Sprague-Dawley rats were randomly divided into four groups. The control group received physiological saline; animals in cisplatin group received only cisplatin; pre-treatment group received a 10-day of lycopene before administration of cisplatin while animals in post-treatment group received a 5-day of lycopene f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
142
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 33 publications
23
142
0
4
Order By: Relevance
“…Mathews [54] reported that the damage occurred in the cell membrane by hydroxyl radicals induced oxidation. This could also explain the marked degeneration, atrophied ovary and decrease number of viable follicles reported in this study which are in line with several reports [23,25,[55][56][57].…”
Section: The Biochemical Effectssupporting
confidence: 93%
“…Mathews [54] reported that the damage occurred in the cell membrane by hydroxyl radicals induced oxidation. This could also explain the marked degeneration, atrophied ovary and decrease number of viable follicles reported in this study which are in line with several reports [23,25,[55][56][57].…”
Section: The Biochemical Effectssupporting
confidence: 93%
“…All chemicals and reagents were used of analytical grade. Lycopene and furan were dissolved in corn oil according to studies of Ateşşahin et al and Hamadeh et al (Hamadeh et al 2004;Ateşşahin et al 2006). Thirty-five adult male Wistar rats (300 -320 g, 120 days old) were used for this study.…”
Section: Chemicals and Animalsmentioning
confidence: 99%
“…For furan, lycopene and STZ, doses used in this study were chosen according to previous studies (Hamadeh et al 2004;Ateşşahin et al 2006;Schmatz et al 2009). Rats were weighed and randomly allocated into five groups of seven individuals: control group (was fed with 1 mL/kg bw corn oil via gavage for 28 days), diabetic control group (was fed with 1 ml/kg bw/day corn oil via gavage for 28 days), diabetic lycopene group (was given lycopene by gavage at dose of 4 mg/kg bw for 28 days), diabetic furan group (was fed with 40 mg/kg bw by gavage for 28 days), diabetic furan+lycopene group (was fed with 40 mg/kg bw ml/kg bw furan and 4 mg/kg bw lycopene via gavage for 28 days).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Recent studies have shown that different natural antioxidants such as vitamin C, vitamin E, ellagic acid, nigella sativa, lycopen, caffeic acid phenethyl ester prevent cisplatin-induced toxicity. 13,28,[32][33][34][35] In this study, we investigated the effects of the natural antioxidants GSE and OOEO in cisplatin-treated rats by microscopic examination and biochemical assays.…”
Section: Discussionmentioning
confidence: 99%